Pengelolaan Jajanan Sehat Untuk Meningkatkan Pola Makan Sehat Anak Sekolah Dasar - Syahla Rizkia Putri Nur’insyani; Prihantini Prihantini (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
. Management of healthy snacks is one implementation of health education. The management of healthy snacks is contained in the Clean and Healthy Behavior (PHBS) indicator where each school must have good snack management. Education units need to pay attention to the management of healthy snacks in the school environment. This is important because the management of good and healthy snacks has a positive impact on students due to good nutritional intake, one of which comes from snacks. Having good nutrition plays an important role in achieving quality human resources. Management of healthy snacks can be done by supervising the food being sold, paying attention to the cleanliness of the canteen and providing training for canteen staff. Therefore, education units must have good and healthy snack management so that they are able to teach health values ​​to children as early as possible and students will get healthy and good nutrition through the snacks they consume daily